Natural products as sources of acetylcholinesterase inhibitors: Synthesis, biological activities, and molecular docking studies of osthole-based ester derivatives - Yu, Xiang; Zhang, Yan; Zhang, Minjie; Chen, Yafang; Yang, Wude (Frontiers in Plant Science, 2022)
Osthole, a natural coumarin compound with extensive pharmacological activities, is a functional component of Cnidium monnieri (L.) Cusson. In a continuous effort to develop new acetylcholinesterase inhibitors from natural products, eighteen osthole esters were designed, synthesized, and confirmed by 1H NMR, 13C NMR and HRMS. These derivatives were shown to inhibit acetylcholinesterase at a concentration of 1.0 mol/mL in vitro, 4m and 4o had moderate inhibitory activities with 68.8% and 62.6%, respectively. Molecular docking study results further revealed AChE interacted optimally with docking poses 4m and 4o. Network pharmacology also predicted that compound 4m could be involved in Ras signaling pathway, which made it a potential therapeutic target of AD.